Transpiração, modelagem do crescimento e tamanho de amostra para feijão comum sob deficit hídrico no solo - Pohlmann, Valeria (2021)
The research aims to model growth and evaluate the response in transpiration, growth, and productivity of bean genotypes under soil water deficit conditions. Two experiments were carried out, experiment 1 (EI) August- December 2019 season, and experiment 2 (EII) January-April 2020 fallow season. The experiments were conducted in a greenhouse in pots with an 8 L capacity within a completely randomized design. Each experiment was bifactorial (cultivars: Triunfo, Garapiá, and FC104; water condition: irrigated and non-irrigated). The water deficit was forced in R5 for all cultivars in EI and Triunfo and Garapiá in EII, and for EII was imposed in V4 for FC104. The fraction of transpirable soil water (FTSW) methodology was used, in which plants were kept in these water conditions until non-irrigated plants reached 10% of the relative transpiration of the irrigated plants when they were again maintained in field capacity until harvest. This methodology was conducted to determine the critical FTSW (FTSWc) of each cultivar to select tolerant water deficit genotypes. Three plants from each treatment were collected biweekly for the aerial part and root morphological evaluations (height stem diameter, number of nodes, root length, dry mass of the aerial part and roots and dry mass of the nodules) in order to adjust logistic growth curves and chanter as a function of the accumulated thermal sum. With these data, more data of fresh mass of the aerial part and roots, number of nodules, fresh mass of the nodules and leaf area, in addition to the growth curves, the number of samples needed to estimate the mean of each character at different levels of amplitude of the confidence interval was determined. Equations were also determined to estimate bean leaf area from the linear measurements of the central leaflet of the trefoil, for which 523 trifoliate trees were collected along with the EI, and the equations validated with 20 trifoliums from each treatment of the EII. Comparing the cultivars Triunfo and Garapiá, it showed tolerance to water deficit, with a higher FTSWc value in EI (0.36) and EII (0.17), nevertheless, in EI, with low atmosphere evaporative demand, both cultivars presented the same productivity, while in the EII, with high atmosphere evaporative demand, Garapiá showed higher productivity. FC104 showed intermediate behavior when it suffered water deficit in R5 and tolerance when in V4, demonstrating the potential of using this super early cultivar as a productive alternative. Between the models, the logistic one is the one indicated to demonstrate the growth of the common bean and it was not possible to determine a general model, because the cultivars, water conditions, and experiments presented different behavior. The sample size is different between characters and between cultivars and water conditions used. To evaluate all the characters analyzed within a 95% confidence interval of up to 40%, 132 plants are required. The general equation LA = 1.092L1.945 can be used in tested conditions without precision loss to estimate common bean leaf area.